Canonical Institutions Suspending the Binding Force of Ecclesiastical Law in Situations of Inability to Observe It - Przytulski, Mateusz (Prawo Kanoniczne, 2025)
In the life of the Church, situations sometimes arise in which the faithful are unable to comply with the requirements of the applicable ecclesiastical law. And although the observance of canon law constitutes the ordinary path for believers, even the inability to observe its provisions does not diminish the supreme law, which is the salvation of souls. The implementation of this highest law is carried out through the canonical institutions of dispensation, dissimulation, tolerance and epikeia. The paper characterises each of these institutions, highlighting their specific features and mutual distinctions.